Ventricular pre-excitation in the general population: a study on the mode of presentation and clinical course. Issue 1 (1st January 2000) - Goudevenos, J A; Katsouras, C S; Graekas, G; Argiri, O; Giogiakas, V; Sideris, D A
Abstract : OBJECTIVE: To describe the mode of presentation and the clinical course of patients with ventricular pre-excitation (Wolff-Parkinson-White (WPW) syndrome), with special emphasis on asymptomatic cases in the general population. METHODS: Over an eight year period (1990–97) a prospective population based survey of cases with WPW pattern was conducted in a defined population in north west Greece (340 000 inhabitants). ECGs with WPW pattern were obtained from a widespread pool of ECGs within the health system. RESULTS: During the study period, 157 cases with WPW pattern were identified (49 female, 108 male). Ages ranged from infants to 84 years, mean (SD) 49.1 (21.0) years in female and 39.6 (20.6) years in male subjects (p < 0.01); 78 (49%) had no history of syndrome related symptoms. Asymptomatic subjects (n = 77; 24 female, 53 male) were older than symptomatic subjects (mean age 46.7 (21.0) v 38.5 (20.6) years, p < 0.03). Documented supraventricular tachycardia was recorded in 27 patients (17%) and atrial fibrillation in 12 (8%) (mean age at first episode 31.2 (18.3) and 51.6 (20.7) years, respectively, p < 0.01). During follow up (mean 55 months) no case of sudden death occurred. Three asymptomatic subjects reported episodes of brief palpitation. CONCLUSIONS: WPW pattern is more common, and diagnosed at a younger age, in men than in women. About half the patients with WPW pattern on ECG are asymptomatic at diagnosis and tend to remain so thereafter. No sudden cardiac death occurred during the study period.